2021
DOI: 10.1103/physrevmaterials.5.014406
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic 3d adatoms on free-standing and Ni(111)-supported graphene

Abstract: We present an extensive density functional theory analysis of the structural, electronic, and magnetic properties of isolated 3d transition metal adatoms (from Ti to Co) adsorbed on free-standing and Ni(111)-supported graphene. We discuss how the energetics of different adsorption sites is influenced by the filling of d-orbital filling across the 3d series and identify a direct correlation between the adatom-graphene distance and the degree of charge transfer. The presence of the Ni substrate is found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
1
Order By: Relevance
“…We thus calculate the adsorption energy of individual Co atom at high symmetry sites on valleys and ridges. Co adsorbs on the center of hexagon (H-site) on the free-standing G sheet [47][48][49] but the presence of the metallic substrate underneath G can alter the favorable adsorption site [50]. On G/Ni(100) we found that hollow sites stay the favorable ones.…”
Section: Distribution Of Co Adatoms and Clusters: Dft Calculationsmentioning
confidence: 87%
“…We thus calculate the adsorption energy of individual Co atom at high symmetry sites on valleys and ridges. Co adsorbs on the center of hexagon (H-site) on the free-standing G sheet [47][48][49] but the presence of the metallic substrate underneath G can alter the favorable adsorption site [50]. On G/Ni(100) we found that hollow sites stay the favorable ones.…”
Section: Distribution Of Co Adatoms and Clusters: Dft Calculationsmentioning
confidence: 87%
“…Since its first synthesis twenty years ago [1,2], graphene has always been the most investigated material thanks to its exotic electronic and mechanical properties, in particular the Dirac fermion characteristic around the Fermi level [3,4]. These unique properties also make graphene an optimal host lattice for a wide variety of adatoms [5,6], which may lead to potential applications such as electronic devices [7], single-ion magnets [8], single-atom catalysts [9], or tuning the electronic properties by doping [10], etc. To step closer to the realization of those applications, it is crucial to understand the behaviors of impurities on graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Итак, в настоящей работе в дополнение к межатомному кулоновскому отталкиванию, способствующему межатомному переходу заряда [4], мы учли внутриатомное отталкивание, ведущее к спиновой поляризации поверхностного димера. Полученные для металлов результаты можно обобщить не только на случай массивных полупроводниковых (диэлектрических) подложек [2], но и на случай двумерных графеноподобных структур [3,4], в связи с чем отметим растущий интерес к исследованию адсорбции магнитных атомов на графене [20][21][22].…”
unclassified